2018
DOI: 10.3176/oil.2018.1.03
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Effects of Fe- And Ca-Based Additives on Gas Evolution During Pyrolysis of Dachengzi Oil Shale of China

Abstract: The pyrolysis of Dachengzi oil shale (OS), Huadian City, China, was carried out in a stainless-steel cylindrical retort at 520 °C both in the absence and presence of catalyst under argon atmosphere to evaluate the catalytic effects of Fe 2 O 3 and CaCO 3 additives on the products yield and characteristics of non-condensable gases. The results showed that the catalyst significantly affected the reactivity of OS kerogen pyrolysis. The shale oil yield increased after adding the catalyst, especially Fe 2 O 3 , but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…93 Wang et al added CaCO 3 and Fe 2 O 3 to kerogen pyrolysis and found that Fe 2 O 3 can increase shale oil yield and reduce gas phase product yield and CaCO 3 can catalyze the secondary cracking of products. 94 Williams and Chishti found that the addition of ZSM-5 increased gas production of oil shale pyrolysis, but the yield of shale oil decreased. The content of polycyclic aromatic hydrocarbons in the oil phase increased, while the content of N and S decreased.…”
Section: Catalysismentioning
confidence: 99%
See 1 more Smart Citation
“…93 Wang et al added CaCO 3 and Fe 2 O 3 to kerogen pyrolysis and found that Fe 2 O 3 can increase shale oil yield and reduce gas phase product yield and CaCO 3 can catalyze the secondary cracking of products. 94 Williams and Chishti found that the addition of ZSM-5 increased gas production of oil shale pyrolysis, but the yield of shale oil decreased. The content of polycyclic aromatic hydrocarbons in the oil phase increased, while the content of N and S decreased.…”
Section: Catalysismentioning
confidence: 99%
“…Yu et al discovered that Co can accelerate the cleavage of C–C bonds in organic compounds, improve the selectivity of aromatic hydrocarbons and promote the aromatization of olefins, thus increasing the content of olefins and aromatic hydrocarbons 93 . Wang et al added CaCO 3 and Fe 2 O 3 to kerogen pyrolysis and found that Fe 2 O 3 can increase shale oil yield and reduce gas phase product yield and CaCO 3 can catalyze the secondary cracking of products 94 . Williams and Chishti found that the addition of ZSM‐5 increased gas production of oil shale pyrolysis, but the yield of shale oil decreased.…”
Section: Factors Influencing Pyrolysis Kinetics Of Solid Fossil Fuels...mentioning
confidence: 99%
“…Therefore, the effect of metal compounds on the yield and quality of liquid products has been studied extensively. Studies have found that Fe, Ca, Zn, Ni, and other metal oxides and chloride can accelerate the pyrolysis of oil shale and promote the generation of hydrogen-free radicals and the lightening of shale oil [ 24 ].…”
Section: Research Progress On Catalytic Pyrolysis Of Oil Shalementioning
confidence: 99%
“…After the Fe 2 O 3 catalyst was added and the CaCO 3 catalyst was added, the shale oil yield also increased in the pyrolysis process, but the shale oil yield was 1.02 times and 1.01 times, respectively. Therefore, Fe 2 O 3 has a stronger catalytic effect on oil shale pyrolysis [ 24 ]. Lu et al [ 12 ] selected CH 3 COONa, (CH 3 COO) 2 Ca, and MgO as oil shale catalysts to study their pyrolysis behavior and characteristics of pyrolysis products.…”
Section: Research Progress On Catalytic Pyrolysis Of Oil Shalementioning
confidence: 99%
“…In our recent theoretical study on the catalytic activity of Cu-doped SBA-15 molecular sieves, we found that the decomposition of organic sulfur compounds can be promoted by doping with Cu [7]. Moreover, research [8] has shown that Fe, Ca, Zn, Ni, and other metal oxides and chloride expedite the pyrolysis of oil shale, facilitate the generation of hydrogen-free radicals, and cause the shale oil to become lighter. Lu et al [9] used MgO as a catalyst to investigate the catalytic pyrolysis of Changji oil shale in Xinjiang and found that the addition of MgO increased the yields of olefins and shale gas CH 4 in shale oil.…”
Section: Introductionmentioning
confidence: 99%